Relationship of some metabolic and hormonal compounds in the blood with the productive and reproductive performance in local Awassi ewes - Al-Rubaei, Hashim M.; Hussein, Makki Khalaf; Jafar, Ali Jasim (Journal of Kerbala for Agricultural Sciences, 2019)
The study was conducted at AL-Fayhaa station in Jabila province (50 km North of Babil) and laboratories of the Department of Animal production techniques for the period from February to June to show the relationship between some metabolic and hormonal compounds in the blood with production and reproductive performance in local awassi ewes. Data were collected from 50 milking ewes 2-5 years old from 220 records of daily milk production for fertility percentage and prolificacy rate. The results showed that the regression coefficient of daily milk production on total protein (dl) and their coefficient reach to 0.0057 kg.mg-1 and prolactin hormone (ml) were positive and highly significant (P<0.01) and their coefficient reach to 0.019 kg.ng-1 and on glucose concentration (dl) were negative and highly significant (P<0.01) and their coefficient reach to - 0.028 kg.mg-1 and on total cholesterol concentration (dl) were negative and significant (P<0.05) and their coefficient reach to - 0.0053 kg.mg-1. The regression coefficient of fertility percentage on follicle stimulation hormone was observed positive and highly significant (P<0.01) and on triglycerides concentration were positive and significant (P<0.05) . the result also showed that the regression coefficient of prolificacy rate on glucose and total protein concentrations were negative and highly significant (P<0.01) . the correlation coefficient between metabolic and hormone compounds in the blood with production and reproductive performance for ewes were supported to the regression coefficient of same traits .we conclude from this study the possibility of using metabolic and hormonal compounds in rapid selection programs to improve head of ewes .